Maternal adjustment in expatriate and non-expatriate contexts: examining the role of sensory processing sensitivity and perceived social support - Lagarrigue, Kalimba Kinti; Sadurní Brugué, Marta; Acevedo, Bianca P.; Betancort, Moises (Frontiers in Psychology, 2025)
Background/purposeThis study examines maternal adjustment in the context of expatriation, where mothers face intensified cultural, social, and psychological challenges. Perceived social support, a key predictor of maternal well-being, may buffer these stressors. Sensory Processing Sensitivity (SPS)—a biological trait associated with heightened environmental and emotional sensitivity—may moderate the influence of maternal adjustment differently depending on the context (expatriation) and perceived social support. This study examines whether SPS and its subscales (Low Sensory Threshold [LST], Ease of Excitation [EOE], and Aesthetic Sensitivity [AES]) influence the link between perceived support and maternal adjustment differently among expatriate and non-expatriate mothers.MethodsParticipants were 279 mothers, ages 20–49, with a mean of 1.9 children (SD = 1.2) aged 0–8 years. Mothers were recruited through targeted advertisements on social media, networks, and forums. Of these, 169 were expatriates, and 110 were non-expatriates. All participants completed measures of maternal adjustment (EMQ), perceived social support (MSPSS), and Sensory Processing Sensitivity (HSP-12 Scale) online.ResultsOverall, SPS and its subdimensions (LST, EOE, and AES) were positively associated with maternal adjustment, with highly sensitive mothers reporting better adjustment than those with lower sensitivity levels. Among expatriate mothers, SPS was a significant predictor of maternal adjustment, and the interaction between SPS and social support significantly predicted maternal adjustment. Also, main effects were observed for each of the SPS subscales (AES, EOE, and LST), with AES and EOE also showing significant interactions with SPS in predicting maternal adjustment. No significant effects of SPS and support, or their interaction and were found for non-expatriate mothers.ConclusionThis study highlights the complex interplay between social support, SPS, and maternal adjustment, demonstrating that sensitivity shapes how mothers experience and benefit from social support. Overall, SPS was associated with better maternal adjustment. Also, in the context of expatriation (with additional challenges), SPS and its interaction with support were associated with better maternal adjustment. These findings suggest a positive outlook for mothers with high SPS, especially in contexts with social support. Also, they highlight the need for targeted interventions tailored to highly sensitive mothers, particularly those in expatriate contexts, to enhance maternal well-being and facilitate adjustment to motherhood.